2006
DOI: 10.1590/s0036-46652006000400010
|View full text |Cite
|
Sign up to set email alerts
|

Does Cleome droserifolia have anti-schistosomiasis mansoni activity?

Abstract: SUMMARYThe present study was undertaken to assess the effect of the crude extract of Cleome droserifolia (CD) leaves on experimentally infected mice with Schistosoma mansoni. Two groups of mice, showing a patent infection of S. mansoni, one of them was daily treated with an alcoholic extract of CD leaves (0.31 g kg -1 body weight, i.p.) for 21 days. The schistosomicidal activity of the CD extract was evaluated, three weeks post-treatment, on some parasitological and histopathological aspects including worm loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…There are relatively few reports in the literature that show in vivo schistosomicidal activity of plant extracts [35, 36]. For example, artemether, an artemisinin derivative, used as a prophylactic agent against schistosomiasis japonica in China, at a concentration of 400 mg/kg, was able to reduce 60% of total worms during six days of treatment, in an experimental model [34].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are relatively few reports in the literature that show in vivo schistosomicidal activity of plant extracts [35, 36]. For example, artemether, an artemisinin derivative, used as a prophylactic agent against schistosomiasis japonica in China, at a concentration of 400 mg/kg, was able to reduce 60% of total worms during six days of treatment, in an experimental model [34].…”
Section: Resultsmentioning
confidence: 99%
“…For example, artemether, an artemisinin derivative, used as a prophylactic agent against schistosomiasis japonica in China, at a concentration of 400 mg/kg, was able to reduce 60% of total worms during six days of treatment, in an experimental model [34]. El-Shenawy et al [36] demonstrated that an alcoholic extract of Cleome droserifolia (Forssk.) Del.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been reported that schistosomiasis causes an impairment of liver GSH content. As a consequence, the antioxidant capacity of the liver decreases, leading to the generation of lipid peroxides that may play a pivotal role in the pathology associated with schistosomiasis (El-Shenawy et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the GSH may be required in order to protect the organism of free radicals formed around the eggs. Thus, glutathione is consumed, justifying the reduced levels found (El-Shenawy et al 2006).…”
Section: Discussionmentioning
confidence: 99%